Prevalence of levator ani muscle injuries in primiparous women after delivery and their influence on pelvic floor disorders: systematic review - Pessoa, Patrícia (2024)
Background: Studies show a significant association between the first vaginal delivery and injuries of the levator ani muscle (LAM), which can cause pelvic floor disorders (PFDs). Objectives: This study aims to identify the prevalence of short and long-term LAM injuries after vaginal delivery in primiparous women and its influence on PFDs. Method: A systematic review was conducted according to the PRISMA methodology. The databases used were Pubmed, Cochrane, and PEDro. The quality assessment of the evidence was carried out using the Critical Appraisal Skills Programme (CASP). Both the selection of studies and their evaluation were done by two researchers and a third reviewer in cases of disagreement. Results: From the search, 57 articles were gathered, and 19 were included to match the eligibility criteria. The prevalence of avulsion of the LAM was found in association with vaginal delivery between 13% and 28% ≤ 1 year after delivery and between 16% and 29% > 1 year after delivery. Ballooning was detected between 20% and 37% ≤ 1 year, and 33% of women > 1 year after delivery, appearing to be more common when compared to avulsion. Pelvic organ prolapse (POP) was considered the most common disorder associated with injuries of the LAM, and there seems to be some connection with sexual dysfunction. Conclusion: Avulsion of the LAM and ballooning of the hiatal area have a high prevalence in primiparous women after vaginal delivery and have a strong direct relation to the development of POP.